2012
DOI: 10.1186/1742-2094-9-81
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of simvastatin in an experimental model of spinal cord trauma: involvement of PPAR-α

Abstract: BackgroundStatins such as simvastatin are inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase used in the prevention of cardiovascular disease. In addition to their cholesterol-lowering activities, statins exert pleiotropic anti-inflammatory effects, which might contribute to their beneficial effects on lipid-unrelated inflammatory diseases. Recently it has been demonstrated that the peroxisome proliferator-activated receptor (PPAR)-α mediates anti-inflammatory effects of simvastatin in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 73 publications
1
45
0
1
Order By: Relevance
“…In the present study, we showed that GW6471 did not significantly counteract the effect of PEA on intestinal motility, although the effect of PEA was lost in GW6471-treated rats. The dose of GW6471 used in the present study has been previously shown to reveal PPARα-mediated anti-inflammatory effects of simvastatin (Esposito et al, 2012).…”
Section: Figure 10mentioning
confidence: 95%
“…In the present study, we showed that GW6471 did not significantly counteract the effect of PEA on intestinal motility, although the effect of PEA was lost in GW6471-treated rats. The dose of GW6471 used in the present study has been previously shown to reveal PPARα-mediated anti-inflammatory effects of simvastatin (Esposito et al, 2012).…”
Section: Figure 10mentioning
confidence: 95%
“…In immune cells, PPARa primarily functions as an inhibitor of inflammatory pathways (4) and is found to be involved in the anti-inflammatory activity of cholesterollowering statin therapy (28). It is further hypothesized that PPARa in T cells may provide an explanation for the observation that women are being generally more susceptible to develop autoimmune diseases than men (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bound antibodies were viewed under an Olympus BX51 microscope. Immunocytochemistry photographs were assessed by densitometry as described previously [14] and analyzed using Image Pro-Plus 6.0 software (Media Cybernetics Company, Silver Spring, USA). The total OD value and area of intracellular brown staining for each section were measured.…”
Section: Male Apoementioning
confidence: 99%